2019–2020 Florida Citrus Production Guide: Pesticide Application Technology: ABE-356/CG024, rev. 3/2019 - Salyani, Masoud (EDIS, 2019)
This 8-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Masoud Salyani and published by the Department of Agricultural and Biological Engineering, March 2019. ABE-356/CG024: 2022–2023 Florida Citrus Production Guide: Pesticide Application Technology (ufl.edu)